Traditional uses and pharmacological activities of Sterculia villosa Roxb. - an underutilized tree of south east Asia - Singh, Akoijam Benjamin; Singh, Puyam Devanda; Vanlalmalsawmropuia, H; Kumar, Suresh; Khanduri, Vinod Prasad; Kumar, Kewat Sanjay (Ethnobotany Research and Applications, 2024)
Background: Sterculia villosa Roxb., is a multipurpose, fast-growing, underutilized tree species. Almost all parts of the trees are traditionally used across its geographically distributed regions by ethnic communities to treat a variety of human ailments and for ethnoveterinary purposes. Methods: Despite extensive ethnomedicinal and pharmacological investigations on S. villosa, there is a notable absence of a comprehensive article consolidating reviews of published literature. So, herein, we designed this review article to provide a systematic and comprehensive analysis of the current research progress on S. villosa, to provide new insights and a broad field of view for future research. Extensive literature searches using “Sterculia villosa," “ethno-veterinary use," “ethnomedicinal use," “phytochemicals," and “pharmacological” were performed on PubMed, ScienceDirect, Scopus, and Web of Science. Results: This plant contains a wide variety of phytochemical constituents (alkaloids, glycosides, steroids, flavonoids, polyphenols, tannins, saponins, and terpenoids). Flavonoids such as Diosmetin, Chrysoeriol and its glucosides derivatives, triterpenoids such as lupeol and cyclopropenoid fatty acids such as palmitoleic acid, oleic acid, linoleic acid, and palmitic acid are beneficial to human health, and are responsible for their antioxidant, anticancer, antimicrobial, immunomodulatory, and anti-inflammatory effects. It is widely reported for treating skin ailments, rheumatism and urinary problems, seminal weakness, impotency, and gastric troubles. Conclusions: S. villosa can be a potential raw material for pharmaceuticals, plywood, pulp and paper industries, and waste water treatment, besides its significant ethno-medicinal uses. Henceforth, the socio-cultural, economic, and ecological values of S. villosa enhance the livelihood of local inhabitants and achieve sustainable developmental goals. Keywords: Diosmetin, palmitoleic acid, antioxidant, premature ejaculation, impotency